Investigating the Association Between Health Literacy and Quality of Life Among Patients With Heart Failure Hospitalized in Coronary Care Unit at Selected Hospitals in Tehran, Iran - Mehri Abdi (Qom University of Medical Sciences, 2021)
Background and Objectives: Symptoms of heart failure and its complications over time cause limitations in the normal life process of patients and may affect their quality of life. Thus, this study aimed to investigate the relationship between health literacy and patientschr('39') quality of life with heart failure admitted to the intensive care units in selected hospitals in Tehran City, Iran. Methods: In this study, 105 patients with heart failure were selected. They were admitted to the cardiac ICU in educational hospitals in Tehran. Data collection tools were demographic information, heart failure health literacy, and quality of life questionnaires. Descriptive statistics and statistical methods of correlation and regression were performed using SPSS v. 24. Results: The results showed a significant positive relationship (r= 0.40) between health literacy and quality of life scores in patients with heart failure. Also, health literacy significantly predicted the quality of life score in patients with heart failure (P<0.001). The results of bivariate regression analysis showed that health literacy scores significantly predict the quality of life of patients with heart failure (P<0.001, r2= 0.16). Conclusion: The findings showed that health literacy could predict the quality of life in patients with heart failure. So, it is crucial to consider health literacy in health promotion programs and improve the quality of life of these patients.